Reproductive indicators of the endemic species Astyanax bifasciatus (Teleostei: Characidae) in a tributary of the Lower Iguaçu River Basin, Brazil - Oliveira, Elton Celton de; Auache-Filho, Alexandre Augusto; Damasio, Denis; Ghisi, Nédia de Castilhos; Michels-Souza, Maria Antônia (Acta Scientiarum. Biological Sciences, 2019)
The reproductive process promotes morphophysiological and behavioral changes in fish species throughout their life cycle. Its success is vital to define their resilience in the environment. This study aimed to evaluate the reproductive biology of the endemic fish species Astyanax bifasciatus in a tributary of the Lower Iguaçu River Basin, Paraná, Brazil. Fish were collected monthly at four sites along the Jirau Alto River in the city of Dois Vizinhos from October 2015 to September 2016. A standardized catch effort with gill nets and fish traps was used. In the laboratory, standard length and total weight were recorded. After anesthesia, the animals were sectioned to macroscopically determine the sex, sexual maturity stage, and presence of celomatic fat. The gonads and liver were removed to determine the gonadosomatic and hepatosomatic indexes, respectively. A total of 160 individuals (104 females and 56 males) were used. The gonadosomatic index, frequency of the gonadal maturation stages, and condition factor showed a long reproductive period with two investment cycles for both sex. Length at first sexual maturity was 4.57 cm for females and 3.56 cm for males. The reproductive data corroborate the generalist profile of the species and demonstrate a high degree of adaptive capacity, even in smaller tributaries.